Assessment of toxicity and biodegradability on activated sludge of priority and emerging pollutants. Issue 6 (18th March 2016) - Tobajas, Montserrat; Verdugo, Verónica; Polo, Alicia M.; Rodriguez, Juan J.; Mohedano, Angel F.
ABSTRACT: Several methods for evaluating the toxicity and biodegradability of hazardous pollutants (chlorinated compounds, chemical additives and pharmaceuticals) have been studied in this work. Different bioassays using representative bacteria of marine and terrestrial ecosystems such as Vibrio fischeri and Pseudomonas putida have been used to assess the ecotoxicity. Activated sludge was used to analyse the effect of those pollutants in a biological reactor of a sewage treatment plant (STP). The results demonstrate that none of the compounds is toxic to activated sludge, except ofloxacin to P. putida . The additives tested can be considered moderately toxic according to the more sensitive V. fischeri assays, whereas the EC50 values of the pharmaceuticals depend on the specific microorganism used in each test. Regarding the biodegradability, respirometric measurements were carried out for fast biodegradability assessment and the Zahn–Wellens test for inherent biodegradability. The evolution of the specific oxygen uptake rate (SOUR) showed that only diethyl phthalate was easily biodegradable and acetylsalicylic acid was partially biodegradable (98% and 65% degradation, respectively). The persistence of dichloromethane, ofloxacin and hidrochlorothiazide was confirmed along the 28 days of the Zahn-Wellens test whereas 1, 1, 1-trichloroethane showed inherent biodegradability (74% removal). Most of the chlorinated compounds, pharmaceuticals, bisphenol A and ethylenediaminetetraacetic acid were partially degraded in 28 d with total organic carbon (TOC) reduction ranging from 21% to 51%. Sulphamethoxazole showed certain biodegradation (50% removal) with TOC decrease around 31%, which indicates the formation of non-biodegradable by-products.